PENGARUH PENGALAMAN OTENTIK DAN PLACE ATTACHMENT TERHADAP NIAT BERKUNJUNG PADA PARIWISATA VIRTUAL - Taufiq Hidayat; Zia Kemala (Bogor Hospitality Journal, 2023)
Authentic experiences are an important factor in virtual reality tourism. The quality of authenticity is very important to enhance the VR tourist experience because some tourism experiences involving VR tourism activities may not be perceived as authentic due to the poor quality of the technology used. Place attachment is a basic human need that has a significant influence on consumer behavior when choosing tourist destinations. This research examines the attachment of authentic experiences to VR tourism experiences as a response, and behavioral intentions among tourists. The aim of this research is to explore the influence of authentic experiences and place attachment to a place on intention to visit virtual reality tourism activities. This research model was carried out using a survey method. The number of respondents was 89 using the convenience sampling technique. The results of the coefficient of determination of the role of authentic experience and place attachment on intention to visit show 48.1%. Correlation coefficient has a positive, which also depicts a positive direction of influence, namely, the better the authentic experience and place attachment, the more influence it has on intention to visit the destination. The coefficient of determination of authentic experience and place attachment on intention to visit virtual reality tourism is 0.481. This value shows that 48.1% of visiting intentions are influenced by the role of authentic experiences and place attachment, while the remaining 51.9% is determined by other factors outside of this research. Keywords: Virtual Reality Tourism; Authentic Experience; Attachment; Intention to Visit